2022
DOI: 10.1093/ajcn/nqac203
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbohydrate vegan diets in diabetes for weight loss and sustainability: a randomized controlled trial

Abstract: Background Low-carbohydrate, high animal fat and protein diets have been promoted for weight loss and diabetes treatment. We therefore tested the effect of a low-carbohydrate vegan diet in diabetes as a potentially healthier and more ecologically sustainable low-carbohydrate option. Objectives We sought to compare the effectiveness of a low-carbohydrate vegan diet with a moderate-carbohydrate vegetarian diet on weight loss an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Finally, the researchers evaluated various health benefits (e.g., BM loss, effect on cardiovascular/type 2 diabetes risk factors and disease outcomes) and potential risks or limitations of recently trendy dietary patterns (i.e., low-carbohydrate, high-fat (ketogenic) diet [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ], Mediterranean diet [ 57 , 58 ], vegetarian diet [ 56 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] and omnivorous diet [ 21 , 66 ]). The weight of evidence strongly supports a balanced (well-designed) diet and simultaneously allows for various variations and interpretations of research results.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the researchers evaluated various health benefits (e.g., BM loss, effect on cardiovascular/type 2 diabetes risk factors and disease outcomes) and potential risks or limitations of recently trendy dietary patterns (i.e., low-carbohydrate, high-fat (ketogenic) diet [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ], Mediterranean diet [ 57 , 58 ], vegetarian diet [ 56 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] and omnivorous diet [ 21 , 66 ]). The weight of evidence strongly supports a balanced (well-designed) diet and simultaneously allows for various variations and interpretations of research results.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that reducing portion size and adopting plant-forward diets, particularly those low in processed items, can be effective strategies for those who wish to reduce weight or avoid weight gain over time. [34][35][36][37][38][39] Both approaches can also support health regardless of body composition.…”
Section: (A) (B)mentioning
confidence: 99%
“…Generally, these studies find that reducing red meat (followed by other meats and dairy) and/or kilocalories leads to the greatest impact on GHGe goals and that compliance with dietary guidelines alone may not result in GHGe reduction 33 . Multiple studies have found that plant‐based and lower‐footprint diets can support weight loss and improved health outcomes 34–39 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AE-S holds shares in Nutrigenomix Inc., however, this did not play a role in AE-S position as a co-author and does not alter our adherence to Frontiers' policies on sharing data and materials. DJ has worked with and had research funded by the food industry (see Jenkins et al, 2022). SM has no conflicts of interest to declare.…”
Section: Data Availability Statementmentioning
confidence: 99%